N-3 PUFA diet enrichment prevents amyloid beta-induced depressive-like phenotype. (March 2018) - Morgese, M.G.; Schiavone, S.; Mhillaj, E.; Bove, M.; Tucci, P.; Trabace, L.
Graphical abstract: Abstract: Among neuropsychiatric diseases, depression is one of the most prevalent. Many pathologies have been indicated as comorbid with depression and in particular, neurodegenerative disorders such as Alzheimer's diseases (AD). In this regard, several evidences endorse a strong relationship between depression and AD, so much that this mental illness has been proposed either as a risk factor for AD or as a prodromic AD phase. Furthermore, amyloid beta (Aβ) peptide, the main constituent of amyloid plaques commonly considered the principal hallmark of AD brains, has been shown to be increased, in its soluble form, in depressed patients. Accordingly, we have previously found that Aβ, intracerebroventricularly (i.c.v.) injected, is able to evoke a depressive-like profile in rats accompanied by low cortical serotonin and reduced neurotrophin content. Taking into account the great increase in AD and depression prevalence, many environmental factors have been under study, particularly dietary factors, and the role of polyunsaturated fatty acids (PUFA) is becoming central in this field of research. Thus, aim of the present study was to evaluate the neurobehavioral effects of lifelong exposure to either n-3 PUFA rich or n-3 PUFA poor diet after Aβ central administration. Results showed that n-3 PUFA enriched diet prevented the Aβ- induced depressive-like behaviors, as reveled by the reduction in the immobility time in the FST test. Furthermore, n-3 PUFA rich diet exposure reverted also serotonin and neurotrophin level reduction in prefrontal cortex of Aβ treated rats. Taken together, our data support the concept that supplementation of diet with n-3 PUFA represents a valid approach to reduce the risk of developing depressive symptoms, as well as reducing the risk of Aβ-related pathologies, such as AD.